Nitrogen Test Tool in Rice Leaves Based on Android Application - Darso, Muhammad; Yudhana, Anton (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
This study aims to make an application for measuring nitrogen requirements in rice leaves based on an android application. The method used is the On Touch Motion Event. The onTouch method will be used when a touch will be sent to be displayed, then MotionEvent contains information about the touch made. System testing is carried out to display images using the Open Camera button using a smartphone camera, after that look for the RGB value then convert it to the BWD scale. This research has succeeded in building an application that can determine nitrogen levels in rice leaves through leaf color and provide recommendations for the amount of fertilization according to the desired results. The results of tests that have been carried out on 6 samples of rice leaves with 60 samples of RGB value data produce an accuracy rate of using the application of 78.33% and the remaining 21.66% is an error value. And how to calculate the land area, the results obtained from the need for urea per plant in 1 ha are 120 kg, where the BWD table shows the value of leaf color on a scale of 2-3 and requires a urea measurement of 100 which is estimated to get a yield rate of 6 t / ha.